The landscape of historical memory : the politics of museums and memorial culture in post-martial law Taiwan - Denton, Kirk A., 1955- (Hong Kong : Hong Kong University Press, 2021)
The divide between East Asia's "Blue Camp" (Nationalist Party) and "Green Camp" (Democratic Progressive Party) has stirred considerable debate about how we should remember Cold War politics in East Asia. Recently, that conversation has been focused on museums. The Landscape of Historical Memory contributes to this ongoing dialogue by analyzing not only the presence of the Blue Camp and the Green Camp in Taiwan's museums but also the state of these museums over the past three decades. The book also considers political involvement in the establishment, architectural design, and historical narratives of museums within the contexts of museums focused on archaeology, history, war, literature, ethnology, and ecosystems; martyrs' shrines; and memorial halls. By examining the political narratives that surround Taiwan's museums, The Landscape of Historical Memory offers readers a compelling exploration of how culture, history, and memory shape identities in Taiwan's postcolonial landscape, the place of museums in a neoliberal economic climate, and the politics of historical memory in an emergent democracy.
Keywords: Museums -- Taiwan; Museums -- Political aspects -- Taiwan; Collective memory -- Taiwan